Control Diversity: How Across-Domain Control Beliefs are Associated with Daily Negative Affect and Differ with Age - Drewelies, Johanna (Psychol Aging, 2019)
Domain-specific control beliefs typically buffer the influence stressors have on people’s negative affect (affective stressor reactivity). However, little is known about the extent to which individuals’ control beliefs vary across stressor types and whether such stressor-related control diversity is adaptive for affective well-being. We thus introduce a control diversity construct (a person-level summary of across-domain control beliefs) and examine how control diversity differs with age and relates to negative affect and affective stressor reactivity. We apply a multilevel model to daily diary data from the National Survey of Daily Experiences (NSDE, N = 2,022; mean age = 56 years; 33–84; 57% women). Our findings indicate that above and beyond average control beliefs, people whose control is spread over fewer stressor domains (less control diversity) have lower negative affect and less affective stressor reactivity. Older adults are more likely than younger adults to have their control beliefs concentrated in one domain. Additionally, associations between control diversity and negative affect and affective stressor reactivity were age invariant. Moderation effects indicated that when people with low average control beliefs are faced with stressors, having control beliefs focused on fewer domains rather than spread broadly across many domains is associated with less negative affect. Our findings suggest that control diversity provides unique insights into how control beliefs differ across adulthood and contribute to affective well-being.